Between Legal Formalism and Responsiveness: Judicial Reasoning on the Status of Children from Unregistered Marriages - Najwa Yazid; Wardah Nuroniyah (Jurnal Syariah dan Hukum Komparatif, 2026)
Unregistered marriages in Indonesia continue to create legal uncertainty regarding the status and civil rights of children. Divergent judicial determinations concerning children born from such marriages demonstrate tensions between legal formalism and responsive approaches to child protection. Employing normative juridical research with statutory, conceptual, and case approaches, the analysis examines three Religious Court determinations concerning child lineage and itsbat nikah. The findings reveal significant disparities in judicial reasoning. One panel adopted a formalistic interpretation by recognizing children only as biological children based on statutory provisions, while another employed a responsive approach by recognizing the material validity of unregistered marriages and prioritizing the best interests of the child. In the itsbat nikah case, the judges granted legalization despite formal administrative limitations to ensure legal certainty and child protection. These differences directly affect children’s rights relating to lineage, inheritance, guardianship, identity, and non-discrimination. Responsive legal approaches provide more comprehensive protection for children born from unregistered marriages.